The attitude in personal financial management practices among undergraduate students / Norzaidani Nordin - Nordin, Norzaidani (2011)
Financial literacy (Jodi George, Financial Education Council) is defined as understanding how to manage money effectively. Financial literacy is the knowledge and skills to make informed decisions regarding money matters. Financial literacy helps an individual fulfil personal, family, social and governmental responsibilities. According to the topic chosen, the attitude in personal financial management practices among undergraduates’ students, the research is conducted to find result for the finding. Research objectives for this study, to determine the level of attitude of undergraduate students toward their personal financial management, to determine whether knowledge influence the attitude of undergraduate students in their personal financial management, and to determine whether parents influence the attitude of undergraduate students in their personal financial management. The scope of the study is mainly focusing on the factors, which are knowledge and parents and whether the both factors is influence the attitude in personal financial management practices by undergraduate students. A set of questionnaires was distributed to the respective respondents. There are 246 set of questionnaires that was distributed to the respondents. Several factors that being discussed in this research are demographic, attitude of undergraduate student toward their financial management, knowledge influence and parents influence. The data is analyzed using descriptive analysis, frequency, reability testing and Pearson correlation of Statiscal package for Social Science (SPSS). The finding shows that the independent variable which are knowledge and parents influence chosen by the researcher for this study have relationship with the attitude of undergraduate students their in financial management. The measure the relationship, the researcher uses the Pearson correlation.